Noni juice reduces lipid peroxidation–derived DNA adducts in heavy smokers - Wang, Mian-Ying (Blackwell Publishing Ltd, 2013)
Food plants provide important phytochemicals which help improve or maintain health through various biological activities, including antioxidant effects. Cigarette smoke–induced oxidative stress leads to the formation of lipid hydroperoxides (LOOHs) and their decomposition product malondialdehyde (MDA), both of which cause oxidative damage to DNA. Two hundred forty-five heavy cigarette smokers completed a randomized, double-blind, placebo-controlled clinical trial designed to investigate the effect of noni juice on LOOH- and MDA-DNA adducts in peripheral blood lymphocytes (PBLs). Volunteers drank noni juice or a fruit juice placebo every day for 1 month. DNA adducts were measured by (32)P postlabeling analysis. Drinking 29.5–118 mL of noni juice significantly reduced adducts by 44.6–57.4%. The placebo, which was devoid of iridoid glycosides, did not significantly influence LOOH- and MDA-DNA adduct levels in current smokers. Noni juice was able to mitigate oxidative damage of DNA in current heavy smokers, an activity associated with the presence of iridoids.